Genetic effects on molecular network states explain complex traits - Matthias Weith; Jan Großbach; Mathieu Clement‐Ziza; Ludovic Gillet; María Rodríguez‐López; Samuel Marguerat; Christopher T Workman; Paola Picotti; Jürg Bähler; Ruedi Aebersold; Andreas Beyer (Molecular Systems Biology)
Abstract The complexity of many cellular and organismal traits results from the integration of genetic and environmental factors via molecular networks. Network structure and effect propagation are best understood at the level of functional modules, but so far, no concept has been established to include the global network state. Here, we show when and how genetic perturbations lead to molecular changes that are confined to small parts of a network versus when they lead to modulation of network states. Integrating multi‐omics profiling of genetically heterogeneous budding and fission yeast strains with an array of cellular traits identified a central state transition of the yeast molecular network that is related to PKA and TOR (PT) signaling. Genetic variants affecting this PT state globally shifted the molecular network along a single‐dimensional axis, thereby modulating processes including energy and amino acid metabolism, transcription, translation, cell cycle control, and cellular stress response. We propose that genetic effects can propagate through large parts of molecular networks because of the functional requirement to centrally coordinate the activity of fundamental cellular processes.